Pandangan Tokoh Ormas NU Dan LDII Kota Bandar Lampung Terhadap Hukum Program Keluarga Berencana (KB) - Muhammad Iqbal Abdussalam; Zezen Zainul Ali (Universitas Islam Lamongan, 2022)
AbstractThis article discusses the opinions of NU and LDII mass organizations in Bandar Lampung City on the Family Planning program which is an effort to regulate the birth rate. NU and LDII figures think that the implementation of family planning is legal as long as it contains elements of benefit. Meanwhile, the practice of family planning is an effort to reduce the birth rate as long as it does not conflict with the Qur'an and Hadith. The author chose the two mass organizations by considering several aspects. First, the NU mass organization is a large mass organization while LDII is a minority mass organization, so this research is more diverse and viewed from two perspectives. This paper is field research, with a descriptive-qualitative research method using a comparative study between the two organizations. So it was found that several aspects have been carried out by the two organizations where the legal aspects allow it as long as it does not conflict with the texts, the objective aspect is due to improve the quality of generations, and the economic aspect is that there is no reason for family planning because they fall into poverty, the binding aspect is subject to government and state aspects, namely, this policy in Islam is known as the ulil Amri policy where every policy must pay attention to the benefit of citizens.